The Influence of Tube Thickness on the Shell Side of the Air preheater As a Form of Corrosion Prevention - Ulyasa, Kinanti; Slameto, Slameto; Widarti, Sri (Fluida, 2023)
Air preheater as a heat recovery technology is generally applied in the powerplant industry and used to heat combustion air, which increases the efficiency of the combustion chamber in the boiler. In this case, air preheater has tubular recuperative type typically located at the bottom of the circulating fluidized boiler for utilizing the lowest temperature exhaust gas. A significant presence of SO2 in the exhaust gas can lead to cold-end corrosion and cause leaks. The low tube thickness in the air preheater provides a good heat transfer performance unfortunately the corrosion issue has not been considered. By increasing the tube thickness, its aimed to extend the life time of the tubes with good corrosion resistance. This study is performed with calculations using empirical equations and validated results using Heat Transfer Research Inc (HTRI) software. Increasing the tube thickness impacts decreasing the heat transfer coefficient, increasing the flue gas (shell) pressure drop, and increasing the fouling factor. The tube thickness which determined for the corrosion prevention design of the air preheater give an overdesign of 18.14%, a heat transfer rate coefficient of 1.726 Btu/hr. ft2. Â°F, a shell pressure drop of 0.000541 psi, and a fouling factor of 0.114 hr. ft2. Â°F/Btu.